Characteristics of Nursing Homes with Comprehensive Antibiotic Stewardship Programs, Results of a National Survey - Fu, Caroline J. (Am J Infect Control, 2019)
BACKGROUND: Antibiotic stewardship in nursing homes (NHs) is a high priority due to intense antibiotic use and increased risk of adverse events. Updated Centers for Medicare and Medicaid Services (CMS) regulations required NHs to establish antibiotic stewardship programs (ASPs). This study describes the current state of NH ASPs. METHODS: A nationally representative survey of NHs was conducted in 2018. ASP comprehensiveness, infection preventionist (IP) training, participation in Quality Innovation Network-Quality Improvement Organization (QIN-QIO) activities, and facility and staff characteristics were analyzed using weighted descriptive statistics and multinomial regression models. RESULTS: Of 861 NHs, 33.2% had comprehensive (6–7 policies), 41.1% had moderately comprehensive (4–5 policies), and 25.6% had not comprehensive ASPs (≤3 policies). Data collection on antibiotic use was most reported (91.4%); restricting use of specific antibiotics was least reported (19.0%). Comprehensive ASPs were associated with QIN-QIO involvement; moderate and comprehensive ASPs were associated with IP training and high occupancy. DISCUSSION: Immediately following CMS regulation changes, a majority of NHs had moderately comprehensive or comprehensive ASPs. Rates for each policy and infection control-trained IPs increased from previous studies. CONCLUSIONS: NH ASPs are becoming more comprehensive. Infection control training and partnerships with QIN-QIOs can support NHs to increase ASP comprehensiveness.